2016
DOI: 10.1053/j.semperi.2016.03.004
|View full text |Cite
|
Sign up to set email alerts
|

What we have learned about scheduling elective repeat cesarean delivery at term

Abstract: The optimal timing of delivery in the setting of various clinical conditions and scenarios remains one of the most common questions for obstetric providers. Over the past 5-10 years, the optimal timing of delivery at term, particularly for elective repeat cesareans, has been the subject of considerable investigation and discussion. There is an increasing consensus that when women opt for an elective repeat cesarean delivery, it should be performed at term rather than preterm. The recent redefinition of the "te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 26 publications
5
4
0
Order By: Relevance
“…However, the frequency of respiratory distress syndrome was significantly lower for deliveries at 38 weeks or more. This finding is consistent with the result of other studies …”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…However, the frequency of respiratory distress syndrome was significantly lower for deliveries at 38 weeks or more. This finding is consistent with the result of other studies …”
Section: Discussionsupporting
confidence: 94%
“…Regarding the impact of delivery at 37 weeks on neonatal outcome, the present study found that delivery at 38 weeks or later was associated with a lower risk of respiratory distress syndrome, but there was no significant difference in risk of NICU admission in the first 24 hours or in mechanical ventilation. This finding is in agreement with other studies, in which early delivery (at 37 weeks) was associated with a higher risk of neonatal respiratory distress syndrome …”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The extent to which the increase in the number of C-sections could be attributed to medical preference or maternal demand should be a focus of future debates. In this sense, our results contribute to the existing research on this subject and con rm that waiting until 39 weeks for elective C-section is advisable, similar to other ndings around the world (36). It is important to highlight, however, that despite being an increasing trend due to maternal request, performing primary C-sections antepartum can lead to substantial public health implications due to its effects on neonatal outcomes (37)(38)(39).…”
Section: Discussionsupporting
confidence: 82%
“… 1–4 23 Our study importantly adds to the existing data on this subject and confirms the observation from other areas of the world that waiting until 39 weeks for elective CD is advisable. 24 Since more than 25% of primary CDs are performed antepartum in other countries and even much higher in China, and since there is increasing enthusiasm for CDMR in western countries, the timing of primary CD and its effect on neonatal outcomes have substantial public health implications. 14 25…”
Section: Discussionmentioning
confidence: 99%